ANALISIS KEPUASAN KERJA PEGAWAI ADMINISTRASI FAKULTAS EKONOMI UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - Sri Lestari; Untung Kumorohadi; Sudjarwanto Sudjarwanto (Solusi, 2020)
This study aims to determine and analyze the job satisfaction level of administrative staff of Faculty of Economics UNSOED the imposition of performance assessment and determination of hours of work per 16 April 2009. In this research used descriptive method with a single case study approach that is holistic ekploratif. The data used in the form of primary data and secondary data. This study uses the 49 administrative staff of Faculty of Economics UNSOED as respondents. Data were collected by using questionnaires. The results of this study indicate that employees' job satisfaction Faculty of Economics UNSOED administration is at the level of 'satisfaction'. This study provides implications for the leadership of the Faculty of Economics UNSOED to: 1) can keep it going now and make improvements, thereby increasing the level of satisfaction is very pleased at intervals; 2) Satisfaction employees are subject to change at any time, therefore the leadership of the Faculty should always follow all their employees fulfillment.Keywords: Employee Job Satisfaction.